The Economics of Sports - Leeds, Michael (Michael A.); Von Allmen, Peter; Matheson, Victor A. (Routledge, 2023)
"The sports industry provides a seemingly endless set of examples from every area of microeconomics, giving students the opportunity to study economics in a context that holds their interest. Thoroughly updated to reflect the current landscape, The Economics of Sports introduces core economic concepts and theories, and applies them to US and international sports. Divided into five parts, the book focuses on three major areas of the economics of sports: industrial organization, public economics and labor economics. Updates for this seventh edition include: - An entirely new chapter on sports gambling and a fully revised section on intercollegiate sports - Updated material on social justice in sports and the impact of the COVID-19 pandemic on the industry - More coverage of international sports, e-sports, and new biographical sketches This well-presented and accessible text is supported by easy-to-follow pedagogical features, such as end-of-chapter summaries and questions, and a companion website, which offers useful resources for students and instructors. It is the perfect textbook for intermediate and advanced undergraduate and graduate courses in sports economics"--